Two‐dimensional two‐layer shallow water model for dam break flows with significant bed load transport. (16th May 2013) - Swartenbroekx, Catherine; Zech, Yves; Soares‐Frazão, Sandra
SUMMARY: River flow dynamics and sediment transport are intimately interdependent. Their interaction governs a great diversity of flows with significant morphologic consequences. To predict the bed load transport induced by dam break waves, the proposed two‐dimensional (2D) two‐layer shallow water description considers an upper layer made of clear water and a lower layer made of a dense mixture of water and moving grains. Continuity and 2D momentum conservation are written for each layer, which allows the depth‐averaged velocities to be distinct in magnitude and direction in both layers. The model accounts for the grain entrainment across the bed interface and for the mass and momentum exchanges between the flowing layers. The system of governing equations, written so that no loss of hyperbolicity occurs in the conservative part, is solved by a Harten–Lax–Van Leer finite volume scheme on an unstructured triangular mesh. The numerical model is tested against four dam break flows over mobile beds: a theoretical radial problem and three laboratory experiments in 1D and 2D configurations. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : To predict the bed load transport induced by dam break waves over a mobile bed, the proposed two‐dimensional two‐layer shallow water description considers an upper layer made of clear water and a lower layer made of a dense mixture of water and moving grains. The system of governing equations, written so that the conservative part is hyperbolic, is solved by an HLL finite volume scheme on an unstructured triangular mesh. The numerical model is tested against laboratory experiments of waves expanding over sand beds in an abrupt enlargement and over a floodplain.